2021
DOI: 10.3390/genes12030334
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of the APX Gene Family and Its Expression Pattern under Phytohormone Treatment and Abiotic Stress in Populus trichocarpa

Abstract: Ascorbate peroxidase (APX) is a member of class I of the heme-containing peroxidase family. The enzyme plays important roles in scavenging reactive oxygen species for protection against oxidative damage and maintaining normal plant growth and development, as well as in biotic stress responses. In this study, we identified 11 APX genes in the Populus trichocarpa genome using bioinformatic methods. Phylogenetic analysis revealed that the PtrAPX proteins were classifiable into three clades and the members of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 70 publications
2
7
0
Order By: Relevance
“…The results of the phylogenetic tree showed that five genes of subfamily I were located in the peroxisome, two genes of subfamily II were located in chloroplasts/mitochondria, one gene of subfamily III was located in cytoplasm and extracell, and one member of subfamily IV was only located in chloroplasts, indicating that the close relatives may have had the same subcellular localization results ( Figure 2 ). CaAPX3 and CaAPX4 of subfamily II were all located in two chloroplast/mitochondrial organelles, as well as in previous studies of PtrAPX1 and PtrAPX5 in Populus trichocarpa ( Leng et al., 2021 ). CaAPX genes located in peroxisome all contain eight different conserved motifs and have eight to ten exon regions.…”
Section: Discussionsupporting
confidence: 83%
“…The results of the phylogenetic tree showed that five genes of subfamily I were located in the peroxisome, two genes of subfamily II were located in chloroplasts/mitochondria, one gene of subfamily III was located in cytoplasm and extracell, and one member of subfamily IV was only located in chloroplasts, indicating that the close relatives may have had the same subcellular localization results ( Figure 2 ). CaAPX3 and CaAPX4 of subfamily II were all located in two chloroplast/mitochondrial organelles, as well as in previous studies of PtrAPX1 and PtrAPX5 in Populus trichocarpa ( Leng et al., 2021 ). CaAPX genes located in peroxisome all contain eight different conserved motifs and have eight to ten exon regions.…”
Section: Discussionsupporting
confidence: 83%
“…As efficient ROS scavengers, APX and CAT proteins work against multiple biotic and abiotic stresses. Previous studies reported that APX and CAT genes play regulatory roles with respect to tolerance against multiple stresses, such as salt, heat, drought, UV radiation and oxidative stress [ 15 , 29 , 75 ]. We screened the upstream region of APX and CAT genes of both species to mark the cis elements.…”
Section: Discussionmentioning
confidence: 99%
“…The Phytozome and PopGenIE ( http://popgenie.org/chromosome-diagram ) databases were mined for chromosomal location data of PtrCOBLs ( Leng et al., 2021 ). Every single gene was mapped on the representing chromosome based on its position report.…”
Section: Methodsmentioning
confidence: 99%